Relationship Between Childhood Sensory Processing Differences and Quality of Life as Adults - May-Benson, Teresa A.; Teasdale, Alison; Easterbrooks-Dick, Olivia (Frontiers in Psychology, 2022)
Research suggests a relationship between sensory processing, motor skills and quality of life (QOL) in a variety of clinical populations of adults and children. There have been no studies which investigated the relationship of childhood sensory processing and integration and related motor performance (sensori-motor) patterns identified using an Ayres Sensory Integration® (ASI) frame of reference and later QOL of those children as adults. This longitudinal follow-up study examined this relationship. Adult QOL was also examined in relation to current adult sensori-motor patterns. Fifty-three adults who received occupational therapy services as children and were identified as having sensori-motor difficulties at that time and completed a sensory history and a quality-of-life measure as adults. Measures included the OTA the Koomar Center Sensory History (SXHX), Adult/Adolescent Sensory History (ASH), and the World Health Organization Quality of Life - Brief (WHOQOL-BREF). MANCOVA found that Total childhood sensori-motor scores had a small relationship to Physical Health QOL as adults that approached significance. Pearson Correlations found that adults with childhood sensori-motor challenges who report sensori-motor challenges as adults had a moderate significant relationship among overall sensori-motor functioning and Physical Health (r = -.56, p = .018). Visual (r = -.76, p = .001), movement (vestibular) (r = -.48, p =.042) and tactile processing (r = -.63, p = .008) had moderate to large significant relationships with Physical Health. Visual processing (r =-.54, p =.024) was also significantly related to Psychological Health. Motor Coordination trended to significance for Physical Health (r = -.42) and Psychological Health (r = -.41). Conversely, adults who reported typical sensori-motor scores as adults, despite childhood sensori-motor challenges, had a good QOL. Furthermore, similar to previous research, there was a relationship between current visual, movement (vestibular) and tactile (touch) sensory processing and adult Physical and Psychological Health. A multivariate linear regression found Sensory Discrimination and Modulation accounted for one-quarter of the variance in QOL in adults with only Discrimination being statistically significant. Therefore, it is important to consider childhood sensori-motor function as well as adult functioning when examining QOL. Further, heretofore unexamined Sensory Discrimination was found to play a role in adult QOL.